(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

For any elements a and b from a group and any integer n, prove that (a^(-1)*ba)^n = a^(-1) b^n *a

2. Relevant equations

There are no equations given for this particular problem

3. The attempt at a solution

by law of exponents and the distributive property(a^-1 *b*a)= a^-n *b^n *a^n=a^(-n +n)*b^n = a^0 * b^n = b^n

Likewise, a^(-1) * b^n * a^1 = a^(-1+1)* b^n

since (a^-1 *b *a)^n =b^n and since a^-1 * b^n *a^1 = b^n , then (a^-1 * b*a) = (a^-1 *b^n *a^1)

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Group thoery question.

**Physics Forums | Science Articles, Homework Help, Discussion**